Evaluation of energy complementarity in colombia: An analysis of climate variability and non-conventional sources - Orlando Joaqui-Barandica; Diego F. Manotas-Duque; Leonardo Rivera-Cadavid (Results in Engineering)
This study analyzes the interactions between various sources of energy generation and climate variables in Colombia, using Vector Autoregressive Models (VAR) and Generalized Additive Models (GAM). The main objective is to understand the dynamics and complementarity between fossil, hydroelectric, solar and wind energy sources, as well as their relationship with critical climate factors. The results of the VAR model reveal a strong interdependence between fossil and hydroelectric generation. Impulse-response functions show that a shock to fossil generation has a significant and sustained impact on hydropower generation and vice versa, highlighting the role of fossil generation as a backup during periods of water stress. Additionally, patterns of interdependence are observed between fossil generation and renewable sources, especially solar, which is beginning to have a more notable impact on fossil generation. GAM analysis complements these findings by providing a nonlinear perspective on the relationships between variables. Hydroelectric generation is found to be strongly influenced by fossil generation, with a significant negative relationship, suggesting that as hydroelectric generation increases, the need for fossil generation decreases. Furthermore, climatic variables such as solar radiation and water reserves have significant relationships with hydroelectric generation, underlining the dependence of the energy system on climatic conditions. Colombia's energy matrix depends 70 % on hydroelectric generation, which, although sustainable under normal conditions, can become critical during periods of drought. In such scenarios, fossil generation becomes an essential backup. The incorporation of non-conventional renewable energy sources, such as solar and wind, is crucial to diversify the energy matrix and improve the resilience of the system.